2021
DOI: 10.1088/1402-4896/ac3d4f
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic variations in Ba0.5Sr0.5Fe9Ce1Al2O19 hexaferrites at different sintering temperatures

Abstract: M-type hexaferrites has attracted researchers due to their ordinary magnetic properties and utilization as media for magnetic recording and microwave devices. In this study we have synthesized Ba0.5Sr0.5Fe9Ce1Al2O19 via conventional ceramic route. The synthesized material is treated against different temperatures and investigated structurally and magnetically by using several techniques such as X-ray diffraction, Scanning electron microscopy, and VSM respectively. Morphology of samples confirms the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The results showed that there were no secondary phases in the material and that the hexagonal shape of the particles was evident in the micrographs. The SEM images in figure 2 was also confirmed that the samples were homogenously and uniformly distributed [18,30]. Pores present in the images showed the removal of PVA binder.…”
Section: Morphological Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…The results showed that there were no secondary phases in the material and that the hexagonal shape of the particles was evident in the micrographs. The SEM images in figure 2 was also confirmed that the samples were homogenously and uniformly distributed [18,30]. Pores present in the images showed the removal of PVA binder.…”
Section: Morphological Analysissupporting
confidence: 58%
“…The magnetic properties of M-type hexaferrites can be altered by partially substituting Ba 2+ and/or Sr 2+ ions with rare Earth ions including La 3+ , Nd 3+ , and Ce 3+ etc [1-3, 10, 12-15, 24]. In addition to ion substitution, the magnetic properties of M-type hexaferrites can also be influenced by the sintering temperature [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that negligible change was found in the grain size after the introduction of dopants. It implies that in the current scenario doping may involve miscellaneous shapes as compared to size [23]. The average grain size was observed from 500 to 2500 nm.…”
Section: Morphological Analysismentioning
confidence: 80%
“…Few studies published have shown the importance and effects of sintering temperature on magnetic and structural properties of Hexa ferrites [27,28]. In our previous work we showed effects of different sintering temperature on magnetic properties of doped barium hexaferrites [29].…”
Section: Introductionmentioning
confidence: 73%
“…follow the JCPDS#43-0002. The results showed minor change in the intensity also upon the introduction of dopant [31][32][33]. Lattice parameters were obtained using reitveld refinement analysis.…”
Section: Structural Investigationsmentioning
confidence: 99%